Effects of Fixation on Design Education - Erkan Yazıcı, Yasemin (Siyasal Kitabevi, Ankara, Turkey, 2011)
Gestalt researchers argue that associations create cognitive obstacles on the creative problem solving processes and that problem-solvers should free themselves from associations and evaluate the problem at hand from different perspectives. These cognitive obstacles are evaluated under the subject of “fixation”. Experimental studies reveal that fixation has adverse effects on cognitive processes such as recollection, problem solving and creative idea generation. Fixation in the context of design problem solving can arise when designers are fixated on the solutions of similar problems encountered in the past to the problem at hand instead of searching for novel and creative solutions. Therefore, one of the primary objectives of design education is to raise the students’ awareness on the effects of being fixated on past solutions through analogies built on surface similarities or invisible assumptions. This study deals with the effects of fixation on the design processes in the context of architectural design education.
Keywords: Design education; Fixation